Analisis Sistem Tataniaga Cabai Merah di Desa Besakih, Kecamatan Rendang, Kabupaten Karangasem - PUTU SRI ADNYASARI; RATNA KOMALA DEWI; KETUT BUDI SUSRUSA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Analysis of Red Chili Trading System in Besakih Village, Rendang Sub-Districtof Karangasem Regency Besakih village as one of the centers of red chilli production in Karangasem Regencyhas several marketing channels with different prices between producers andconsumers. This study aims to investigate the channels of trading, commercialinstitutions, and the red chili trading system in the Village of Besakih. The data usedwere quantitative and qualitative data. The analysis used descriptive qualitative.Respondents in the study were 38 farmers determined by proportional randomsampling method and 23 respondents of trading institutions determined by snowballsampling method. The research result was six channels of trading system, (1)Farmers – Local Assembly Trader’s - Retailers - Consumers; (2) Farmers - LocalAssembly Trader’s - Retailers - Consumers; (3) Farmers – Sub Terminal ofAgribusiness - Retailers - Consumers; (4) Farmers - Sub Terminal of Agribusiness -Retailers - Consumers; (5) Farmers - Sub Terminal of Agribusiness - Consumers; (6)Farmers - Sub Terminal of Agribusiness – Market in Lombok. The most efficienttrading channel was channel II. The trading agency consists of local assemblytrader’s / inter-city / inter-district traders, Sub Terminal of Agribusiness / inter-city /inter-district / inter island traders, traditional market retailers and supermarketretailers. Each of the trading system institution involved the three main functions ofexchange, physical function and facility function. However, the activities undertakenby each institution were different.